Tailoring lithium-peroxide reaction kinetics with CuN2C2 single-atom moieties for lithium-oxygen batteries. (March 2022) - Li, Xudong; Han, Guokang; Lou, Shuaifeng; Qiang, Zhuomin; Zhu, Jiaming; Ma, Zhongyun; Zuo, Pengjian; Du, Chunyu; Yin, Geping
Abstract: Single-atom catalysts (SACs) featuring maximized atom utilization are, in no doubt, playing an increasingly significant role in aprotic lithium-oxygen batteries (LOBs). However, rational design and construction of SACs active sites remain enormously challenging due to the superficial understanding of their structure-function relationship. In this contribution, we provide new insight into the link between the catalytic effects of catalysts and the detailed nucleation/delithiation mechanisms of Li2 O2 during the oxygen reduction/evolution reaction (ORR/OER). Here, a CuN2 C2 SACs electrocatalyst is tailored for LOBs by a confined self-initiated dispersing strategy. The exposed Cu-N2 moieties as the driving force centers can promote the formation of micron-sized flower-shaped lithium peroxide and further accelerate the decomposition kinetics of lithium peroxide via a one-electron transfer way in turn. Under the catalysis of CuN2 C2 SACs, the LOB can operate with low discharge/charge polarization and long-term cycle stability. These encouraging results provide guidance to future design and activity promotion of efficient catalysts for LOBs. Graphical Abstract: ga1 Atomically dispersed Cu atom with asymmetric coordination environment (CuN2 C2 ) can serve as highly-active & satisfyingly-selective catalytic sites, weakening the intrinsic LiO2 -absorption ability and thus promoting the solution-mediated working principle. Moreover, in the effect of CuN2 C2 SACs electrocatalyst, the initial delithiation of Li2 O2 turned into a single-electron process from the typical two-electron reaction, substantially boosting reaction kinetics. Highlights: For the first time, the single-atom catalyst with CuN2 C2 moieties was tailed as catalyst in Li-O2 batteries systems. The CuN2 C2 can weaken the LiO2 -adsorption ability and promote the solution-mediated discharge mechanism of Li-O2 batteries. The CuN2 C2 can transform the oxidation of Li2 O2 from the typical two-electron process into a single-electron reaction.